Soft cationic nanoparticles for drug delivery: production and cytotoxicity of solid lipid nanoparticles (SLNs) - Silva, Amélia M. (2019)
The surface properties of nanoparticles have decisive influence on their interaction with biological barriers (i.e., living cells), being the concentration and type of surfactant factors to have into account. As a result of different molecular structure, charge, and degree of lipophilicity, different surfactants may interact differently with the cell membrane exhibiting different degrees of cytotoxicity. In this work, the cytotoxicity of two cationic solid lipid nanoparticles (SLNs), differing in the cationic lipids used as surfactants CTAB (cetyltrimethylammonium bromide) or DDAB (dimethyldioctadecylammonium bromide), referred as CTAB-SLNs and DDAB-SLNs, respectively, was assessed against five different human cell lines (Caco-2, HepG2, MCF-7, SV-80, and Y-79). Results showed that the cationic lipids used in SLN production highly influenced the cytotoxic profile of the particles, with CTAB-SLNs being highly cytotoxic even at low concentrations (IC50 < 10 µg/mL, expressed as CTAB amount). DDAB-SLNs produced much lower cytotoxicity, even at longer exposure time (IC50 from 284.06 ± 17.01 µg/mL (SV-80) to 869.88 ± 62.45 µg/mL (MCF-7), at 48 h). To the best of our knowledge, this is the first report that compares the cytotoxic profile of CTAB-SLNs and DDAB-SLNs based on the concentration and time of exposure, using different cell lines. In conclusion, the choice of the right surfactant for biological applications influences the biocompatibility of the nanoparticles. Regardless the type of drug delivery system, not only the cytotoxicity of the drug-loaded nanoparticles should be assessed, but also the blank (non-loaded) nanoparticles as their surface properties play a decisive role both in vitro and in vivo.